Produktivitas dan Ketahanan Galur Harapan Padi terhadap Penyakit Tungro di Sumatera Selatan - Tumarlan Thamrin; Imelda Suryani Marpaung; Syahri Syahri (Jurnal Lahan Suboptimal : Journal of Suboptimal Lands, 2012)
Thamrin et al. 2012. Productivity and Resistancy of the Tungro-resistant Rice Variety in South Sumatra. JLSO 1(2):130-137. The establishment of new varieties is required to have the advantage of being more diverse and specific according to agroecosystem, problems in the field, the specific location and consumers’ preference. Prior to its establishment, a tungro-resistant rice variety needs to be tested locally. This research was carried out on the rain-fed rice field at the village of Lubuk Seberuk Sub-district Lempuing, Ogan Ilir Komering Regency (OKI) in 2009. This research employed randomized block design (RGD) with 10 treatments consisted of eight strains and two improved varieties as a comparison. Each treatment was repeated 3 times. The results indicated that strain B-10018G-TB-42-1 has the least tungro attacks and the highest number of tillers and production compared to the other strains and varieties.